Nonlinear discrete-time hazard models for women's entry into marriage. (February 2022) - Turner, Heather L.; Batchelor, Andy D.; Firth, David
We propose a hazard model for entry into marriage, based on a bell-shaped function to model the dependence on age. We demonstrate near-aliasing in an extension that estimates the support of the hazard and mitigate this via re-parameterization. Our proposed model parameterizes the maximum hazard and corresponding age, thereby facilitating more general models where these features depend on covariates. For data on women's marriages from the Living in Ireland Surveys 1994–2001, this approach captures a reduced propensity to marry over successive cohorts and an increasing delay in the timing of marriage with increasing education.